2018
DOI: 10.1037/bul0000139
|View full text |Cite
|
Sign up to set email alerts
|

Video game training does not enhance cognitive ability: A comprehensive meta-analytic investigation.

Abstract: As a result of considerable potential scientific and societal implications, the possibility of enhancing cognitive ability by training has been one of the most influential topics of cognitive psychology in the last two decades. However, substantial research into the psychology of expertise and a recent series of meta-analytic reviews have suggested that various types of cognitive training (e.g., working memory training) benefit performance only in the trained tasks. The lack of skill generalization from one do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
158
5
10

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(183 citation statements)
references
References 216 publications
10
158
5
10
Order By: Relevance
“…A substantial body of literature, mostly involving studies of young adults, has demonstrated that playing certain types of cognitively demanding video games can produce broad enhancements in perceptual, motor, and cognitive skills (Bediou et al, 2018;Powers, Brooks, Aldrich, Palladino, & Alfieri, 2013; but see Sala, Tatlidil, & Gobet, 2018). Studies of adolescents are fewer in number and have relied more heavily on correlational designs (Dye & Bavelier, 2010;Dye, Green, & Bavelier, 2009;Trick, Jaspers-Fayer, & Sethi, 2005).…”
Section: Media Use During Adolescencementioning
confidence: 99%
“…A substantial body of literature, mostly involving studies of young adults, has demonstrated that playing certain types of cognitively demanding video games can produce broad enhancements in perceptual, motor, and cognitive skills (Bediou et al, 2018;Powers, Brooks, Aldrich, Palladino, & Alfieri, 2013; but see Sala, Tatlidil, & Gobet, 2018). Studies of adolescents are fewer in number and have relied more heavily on correlational designs (Dye & Bavelier, 2010;Dye, Green, & Bavelier, 2009;Trick, Jaspers-Fayer, & Sethi, 2005).…”
Section: Media Use During Adolescencementioning
confidence: 99%
“…By temporarily storing and manipulating information, working memory (WM) is critical to numerous aspects of cognition (Baddeley, 1986). Improved performance on WM through training has been widely expected to transfer to other performances; however, transfer of WM training to different but related tasks is often either absent or negligible, despite gains in trained WM tasks being consistently large (Au et al, 2014;Melby-Lervåg et al, 2016;Sala et al, 2018). Since WM training has little benefit on everyday cognitive functions that depend on WM, training has been thought to be incapable of increasing the fundamental capacity of WM (Martin and Fernberger, 1929;Chase and Ericsson, 1981;Gathercole et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This claim had been challenged, and the findings regarding the advantages of strategic video games have been questioned (e.g. Roque & Boot, 2018;Sala, Tatlidil, & Gobet, 2018). We should note that even if action video game players demonstrate better strategies, it is still not clear whether playing action video games is the reason or the result of this enhanced strategic ability (or both).…”
Section: Resultsmentioning
confidence: 99%